(untitled) (International relations and international law Journal, 2016)
This article covers the issues of relations between the People’s Republic of China and Central Asian region countries within the framework of the SCO. The Central Asian region plays a significant role within the foreign policy strategy of People Republic of China. With an attempt to assimilate and promote China to the EU market, the strong capturing of Central Asian market is a strategic goal for it. The relations between Central Asia and China are taking on new significance in the face of geopolitical confrontation between global centers for the power influence in the region. In the new century, China as a regional leader tends to promote the strategic partnership with its geopolitical counterparts. The development of cooperation with the Central Asian region countries within the framework of multilateral relations, e.g. SCO, and bilateral relations have also become a strategy of the Chinese policy, which is aimed at long-term perspective. To different extents, the Central Asia countries do more clearly experience the growing political, economic and sociocultural impact of China.